Risk and Protective Factors for Externalizing Behavior at 3 Years: Results from the All Our Families Pregnancy Cohort. Issue 7 (September 2018) - Hetherington, Erin; McDonald, Sheila; Racine, Nicole; Tough, Suzanne
ABSTRACT: Objective: This study examines risk and protective factors for externalizing behavior in children aged 3 years to inform early interventions and enhance school readiness. Method: A total of 1314 mothers participating in a longitudinal study completed questionnaires when their children turned 2 years and again at the age of 3 years. Externalizing behavior was assessed using a short version of the Child Behavior Checklist. Risk and protective factors included the child's characteristics, maternal mental health and disposition, socioeconomic status, and community engagement and child care. Logistic regression models produced crude and adjusted odds ratios (AORs). Results: Poor maternal mental health and high levels of maternal neuroticism were associated with an increased risk for externalizing problems at 3 years (AOR, 1.66; 95% confidence interval [CI], 1.16–2.40 and AOR, 2.28; 95% CI, 1.58–3.30). Care by their mother, relative, or a nanny (compared with being in child care) also conferred an increased risk (AOR, 1.38; 95% CI, 1.01–1.90). Mothers' community engagement modified the risk for boys, such that boys whose mothers did not participate in community activities were 4 times more likely to have externalizing problems than did boys whose mothers engaged in community activities. Conclusion: Families in which mothers experience mental health challenges or have dispositional traits that increase the risk of externalizing behaviors can be identified early. Identification provides the opportunity to promote engagement with parenting supports to improve the outcomes of the child and family. Providing opportunities for children to practice their self-regulation skills through participation in child care and community activities promotes development and mitigates the risk of externalizing behavior.